Previous inter-sexual aggression increases female mating propensity in fruit flies. (17th June 2022) - Filice, David C S; Dukas, Reuven
Abstract: Female mate choice is a complex decision making process which involves many context-dependent factors. Understanding the factors which shape variation in female mate choice has important consequences for evolution via sexual selection. In many animals including fruit flies, Drosophila melanogaster, males often use aggressive mating strategies to coerce females into mating, but it is not clear if females' experience with sexual aggression shapes their future behaviors. Here, we used males derived from lineages which were artificially selected to display either low or high sexual aggression toward females to determine how experience with these males shapes subsequent female mate choice. First, we verified which males from these lineages differed in their sexual behaviors. We found which males from high sexual aggression backgrounds spent more time pursuing virgin females, and had a shorter mating latency but shorter copulation duration compared with males from low sexual aggression backgrounds. Next, we tested how either a harassment by or mating experience with males from either a high or low sexual aggression backgrounds influenced subsequent female mate choice behaviors. We found which in both scenarios, females which interacted with high sexual aggression males were more likely and faster to mate with a novel male one day later, regardless of the male's aggression level. These results have important implications for understanding the evolution of flexible polyandry as a mechanism which benefits females. Abstract : Female mate choice is flexible, is shaped by experience, and has important consequences for the evolution of phenotypes. Despite this, little is known about the effects of sexual aggression on subsequent mate choice. We compared the mating behavior of females that experienced courtship and mating from males artificially selected for high and low sexual aggression. We found that females were more likely to mate, and mated faster, a day after experience with a male from a high aggression background.